Bifunctional additive 2-amino-3-hydroxypyridine for stable and high-efficiency tin–lead perovskite solar cells. Issue 1 (9th December 2022) - Chen, Wentao; Su, Kuo; Huang, Yuqiong; Brooks, Keith Gregory; Kinge, Sachin; Zhang, Bao; Feng, Yaqing; Nazeeruddin, Mohammad Khaja; Zhang, Yi
Abstract : A schematic illustration of the interaction between perovskites and AHPD, and the effect of AHPD on the microstructure evolution of the films. Abstract : Tin–lead (Sn–Pb) mixed perovskite has received widespread attention due to its suitable band gap width and high optical absorption coefficients. However, the power conversion efficiency (PCE) of Sn–Pb mixed perovskite solar cells (PSCs) is still low due to the fact that Sn 2+ could be easily oxidized to Sn 4+ and an excessively rapid crystallization rate was observed for the Sn–Pb mixed perovskite materials. Herein, we introduced 2-amino-3-hydroxypyridine (AHPD), which contains a pyridine nitrogen and an –NH2 group in the molecule, as a bidentate anchoring additive in the FA0.7 MA0.3 Pb0.5 Sn0.5 I3 precursor solution to improve device performance. Incorporation of AHPD into the FA0.7 MA0.3 Pb0.5 Sn0.5 I3 precursor solution was found to effectively suppress the Sn 2+ oxidation and thus the p-doping level defects. Furthermore, the pyridine nitrogen and the enamine-like –NH2 could retard the nucleation and crystallization rate by forming a coordinating interaction with PbI2 /SnI2, forming compact large-grained films and also improving the carrier transport by passivation of the grain boundaries. Overall, compared with the control device (a PCE of 15.72%), an optimized device incorporating 2 mol% AHPD exhibited a PCE of 19.18% for narrow band gap perovskite solar cells, an increase of nearly 22%, with a high level of reproducibility.